Nazwy wykonawców czynności – teoria a umiejętności dzieci w wieku przedszkolnym - Lica, Aneta; Walencik-Topiłka, Anna; Lica, Zenon (Papers in Linguistics, 2019)
The article presents an analysis of the competences of the 4-6-year-olds in creating pattern-forming neologisms. The authors concentrate on the category of names of agents performing an action, researching the most popular derivational techniques and word-formation types, as well as the most frequent derivational bases and the relation of the gathered material to the normative forms. The authors are also interested in the readiness of children of a certain age to independently create names of agents. The conducted research can be used for creating diagnostic tools and therapeutic programmes in logopedics.